Penerapan Pemisahan Perkara (Splitsing ) dalam Proses Penyelesaian Tindak Pidana Koneksitas - Hakim, Lukman (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
One of the urgencies of splitting case files into several independent files is intended to place each defendant as a reciprocal witness among themselves. However, it is not uncommon to find that investigators have separated case files before being transferred to the prosecutor's office to be examined and carried out the public prosecution process. The purpose of investigators separating the files is: a) to avoid files going back and forth. b) due to lack of evidence in the case. c) to facilitate the determination of the role of the suspect. d) the possibility that the suspect has not been caught. Meanwhile, the purpose of Splitting by the public prosecutor is to facilitate the public prosecutor in carrying out the obligation to provide evidence at the prosecution stage and making an indictment for the crime of involvement because in this case the case is usually the same but there are no witnesses, and if the public prosecutor does not do Splitting on the files that are being split, the public prosecutor will experience difficulties and then have an impact on the public prosecutor's indictment not being accepted and the defendant being free on legal grounds. The results of the study show the following: First, in the Criminal Procedure Code and Law Number 31 of 1997 concerning Military Justice, it is regulated that splitting or separation of cases in the criminal justice process is the authority of the Public Prosecutor (PU)/Military Prosecutor (Otmil), not the authority of the investigator. Investigators carry out splitting based on requests from the PU/Otmil. Second, the application of splitting is only regulated for perpetrators who are in one jurisdiction of the judicial body. The application of splitting in connectivity cases before the determination of the judicial environment that has the authority to try the connectivity case is contrary to the law, resulting in the consequence that the indictment is null and void.